ART A Hybrid Classification Model. - Berzal, Fernando (Machine learning.)
This paper presents a new family of decision list induction algorithms based on ideas from the association rule mining context. ART, which stands for lsquoAssociation Rule Treersquo, builds decision lists that can be viewed as degenerate, polythetic decision trees. Our method is a generalized ldquoSeparate and Conquerrdquo algorithm suitable for Data Mining applications because it makes use of efficient and scalable association rule mining techniques.